PENDAMPINGAN SERTIFIKASI P-IRT DAN TEKNOLOGI PENGEMASAN PRODUK UNTUK INDUSTRI KECIL “QIFA COOKIES” PEMBUAT PIA MALANG - Iis Siti Aisyah; Laurina Evanale (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
The main problem for new cake entrepreneurs is the traditional way of managing the industry. Because most business people start from small capital, with modest resources, traditional product manufacturing, product packaging is very simple using plastic mica. So the problems faced by new business people will have difficulty competing to win the hearts of consumers. Therefore this assistance was carried out in a number of steps including counseling on production and K3 management, file preparation and registration, counseling from the DHO, visitation and improvement, issuance of P-IRT certificates and attractive and healthy product packaging design. After going through a long stage, in the end the partner succeeded in obtaining 2 P-IRT certificates with the MOH RI number P-IRT number 8063507023008-24 for Apple Pie cakes and number 8063507013008-24 for the Fill Apple Pie cakes Keywords: service, P-IRT, packaging, pia cake.